On the issues of localization and mapping in outdoor unstructured environments for mobile robot navigation - Perera Linthotage Dushantha Lochana (2008)
The localization information is of paramount importance in several critical tasks such as path and mission planning and control, which are essential to achieve fully autonomous operation of mobile robots. Data association, use of multiple sensors, their fusion and effects of exteroceptive and proprioceptive sensor biases are identified as major issues that affect the performance of robot localization and mapping in outdoor unstructured environments. The importance of these issues in localization and mapping of mobile robots in outdoor unstructured environments is investigated in depth both rigorously and comprehensively.